Back-Matter - Jurnal Gizi Indonesia (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition, 2014)
Author Guidelines; Reviewer Acknowledgement; Subjectand Author Indexes; Subscription form; dan Back Cover.